Disability and the Internet in 2015: Where to now? - Ellis, Katie; Kent, Michael (2015)
Earlier this decade, the emerging field of disability media began to focus on the Internet and people with disabilities. Books such as Paul T. Jaeger's Disability and the Internet in 2012 and Disability and new media by this issue's editors in 2011 both extended earlier work in this field particularly Goggin and Newell's 2003 Digital disability.